The use of mind maps as a resource in teaching and learning - Paizan, Silena da Fonseca Pimentel[UNESP] (Fundacao Univ Tocantins, 2022)
The experience report presents a field work developed in the public education network of the State of Stio Paulo, with students of the second year of high school within the curricular component Philosophy. Its objective is the systematization of ideas, application and, therefore, the understanding of the content previously offered by the teacher, respecting the student's subjectivity. In this teaching methodological resource, the student will become the protagonist of his learning, seeking the significance of the contents offered through expository and even dialogic classes. This significance will be contextualized through the composition of mental maps, where students will relate concepts offered in class with their interpretation/experience before them, thus organizing the mental maps that will translate their subjective experience that was a product of the theory of the curricular component and of your world experience. However, after this teaching and learning
Keywords: Experience; Subjectivity; Curricular Components